Managing Business Growth for a Small Business Entity (Case Study : Toko Nata Bahagia, Traditional Convenience Store) - Arianti, Dewi; Welly, John (The Indonesian Journal of Business Administration, 2013)
The increasing amount of global retailers and franchised multi-chain stores in the past decade in Indonesia has tightened the market for independent convenience stores. Modern stores provide affordable prices and a ‘modern look’ store atmosphere that are bright and clean that has shifted the behavior of consumers to leave patronizing traditional markets and stores. The large economy scale of multi-chain stores has gained the advantage of bargaining power with product suppliers through trading terms and has set a different level of trading compared to traditional stores through its product cycle and pricing system. Previous researches had proven that by the increase of modern retailers by 8%, has eliminated traditional kiosks, stores and markets by 30% (AC Nielson data). The objective of this research is to find out how a traditional convenience store can survive the fierce competition of the retail industry. Taking a case study of a single traditional store named Nata Bahagia that has operated for 22 years in North Bandung, this research intends to formulate solutions to manage and increase its business growth. Currently the business issue is that’s the store is in a healthy condition and is progressing an income growth, but as operational costs rise thus making the profit not increasing. By implementing a comprehensive research of Nata Bahagia by studying its business situation (PESTEL & Customer behavior analysis’) and the company situation (Porter’s 5 Forces, Value Chain, & Financial analysis’), the store could find the root causes of the business issue. The result could then be formulated in the strategy formulation analysis by implementing SWOT, Grand Strategy, TOWS, and Internal-External analysis’. The result is that to manage the company’s business growth the store has to improve their productivity and is in a good condition to increase their business growth. Productivity is implemented by reducing operational costs and increasing sales. One of the programs to increase sales is by improving their delivery service and accommodating local & domestic homemade products to add cost advantage. To expand the company’s business growth, since the store is locally well known, the best is a social approach by creating a facility that could help provide welfare for the society which is by making a basic-need wholesaler (currently does not exist in the area). The purpose is to solve the problem that many small-medium enterprises (SME) face when purchasing to suppliers, no bargaining power. By collecting the many small-volume purchases of these SME’s, the wholesaler would gain bargaining power and issue trading terms. Keywords : retail industry, convenience store, small-medium enterprises, PESTEL, customer behavior analysis, Porter’s 5 Forces, Value Chain, SWOT, Grand Strategy, TOWS, Internal-External